SPINAL ANESTHESIA ONSET OF SENSORY BLOCK OF CERVICAL CANCER BRACHYTHERAPY OUTPATIENT CLINIC: COMPARISON OF 5 MG HYPERBARIC BUPIVACAINE FENTANYL WITH 2,5 MG HYPERBARIC BUPIVACAINE AND 25 MCG FENTANYL - Rica DM; Mafiana R; Zainal R; Bahar E; Irfan AK (Majalah Kedokteran Sriwijaya, 2024)
Spinal anesthesia is the technique of choice for ambulatory anesthesia in cervical cancer brachytherapy patients. Low-dose local anesthetics can speed up the ambulation time. This study aims to compare the onset time of low-dose spinal anesthesia with conventional doses. This study was a double-blind, randomized controlled trial conducted in August – September 2022 at the Radiotherapy Installation of Dr Mohammad Hoesin Hospital (RSMH) Palembang. All cervical cancer patients undergoing brachytherapy in adults with ASA I-II physical status were included in the study sample. Samples will be randomized into two groups, namely a combination of hyperbaric bupivacaine 5 mg and fentanyl 25 mcg and a group of bupivacaine 2.5 mg and fentanyl 25 mcg. Patients with allergies, impaired motor function, spinal failure, block level not achieved, shock, apnea, respiratory depression, and experiencing pain during the procedure were excluded from the study.The onset of sensory block with hyperbaric bupivacaine 5 mg and fentanyl 25 mcg was faster than bupivacaine 2.5 mg hyperbaric and fentanyl 25 mcg (5.388 ± 0.60 versus 10.47 ± 2.06 minutes) The onset of sensory block in the hyperbaric 5 mg bupivacaine and 25 mcg fentanyl group was faster than the hyperbaric bupivacaine 2.5 mg and 25 mcg.